Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Cash Holding pada Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia - Kharisa Kharisa; Muhammad Iqbal Pribadi; Rahman Anshari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study examines the effect of profitability and company size on cash holding. The method in this study uses panel data regression and in collecting data using purposive sampling techniques. The main population in this study used the consumer cyclicals subsector from 166 companies and obtained a sample of 107 companies, during the research period starting in 2021-2023 so that the observation data was 321. In research cash holding is measured using cash and cash equivalents / total assets, profitability using Return on assets (ROA), company size is measured using Size. The results of this study indicate that profitability has a significant positive effect on cash holding, while company size also has a significant positive effect on cash holding.